2014
DOI: 10.16965/ijar.2014.504
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sacral Index: Comparison Between Different Regional Populations of India and Abroad

Abstract: Identification of sex by human skeletal remains is a critical problem and is very important in anthropological and medico legal works. Bones often survive the process of decay and therefore provide the major evidence of human age and sex after death. Over the years different authors had carried various types of measurements on human sacra of different races and regions. The present study carried out 81 sacra of unknown sex contains 45 male and 36 female sacra identified by physical characteristics. They were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 3 publications
0
4
0
6
Order By: Relevance
“…Asthana et al (2014) [14] used sacral index to differentiate the two sexes in western Indian populations of Jaipur and Bikaner (Rajasthan). Janipati et al (2014) [16] studied the sacral index among populations of Telangana and Andhra Pradesh and compared with various Indian populations and found it higher in Telangana and Andhra Pradesh. They concluded that the mean sacral index in females is higher than that of males in Indian populations.…”
Section: Metric Study and Discussionmentioning
confidence: 99%
“…Asthana et al (2014) [14] used sacral index to differentiate the two sexes in western Indian populations of Jaipur and Bikaner (Rajasthan). Janipati et al (2014) [16] studied the sacral index among populations of Telangana and Andhra Pradesh and compared with various Indian populations and found it higher in Telangana and Andhra Pradesh. They concluded that the mean sacral index in females is higher than that of males in Indian populations.…”
Section: Metric Study and Discussionmentioning
confidence: 99%
“…Mean in male sacrum was 98.35 and in female sacrum 113.5. According to Poornima et al 4 in Andhra Pradesh and Telangana regions related to southern part of India values of sacral index in males is 104.08 and females is 115.72. The % of bone identified as male sacrum was 64% and the % of bone identified as female sacrum was 68%.…”
Section: Sacral Index Methodsmentioning
confidence: 98%
“…Os sacrum'un maksimum uzunluğu: Mid-sagital düzlemde promontorium ile os sacrum'un ön kenarının en alt noktası (apeks) arasındaki uzaklık hesaplandı [13][14][15][16][17]18,[19][20][21][22][23][24] .…”
Section: Uygulamaunclassified
“…Sakral indeks: (Os sacrum'un maksimum genişliği / os sacrum'un maksimum uzunluğu) x 100 15,16,[20][21][22][23] şeklinde hesaplandı.…”
Section: Uygulamaunclassified
See 1 more Smart Citation